MODEL PEMBERDAYAAN IBU RUMAH TANGGA DALAM KOLABORASI PENGELOLAAN SAMPAH DI BANK SAMPAH SIPAKARANNU - Yusrawati, Yusrawati; Suhaeb, Firdaus W (UNM Geographic Journal, 2023)
This study aims to find out: how the model of empowering housewives in waste management collaboration at the Sipakannu waste bank, Sambung Jawa Village. This research uses qualitative methods with a descriptive approach. The number of informants in this study was 5 people determined by purposive sampling techniques with criteria 1) Involved and knowing the process of organizing housewife empowerment at the Sipakarannu Waste Bank, 2) Responsible for the implementation of housewife empowerment at the Sipakarannu Waste Bank, 3) Willing to be a research subject for researchers. The data collection techniques used in this study were observation, interview and documentation methods. 3-step qualitative data analysis techniques include data reduction, data presentation, and conclusions. The results of this study show that: the empowerment of housewives carried out at the Sipacarannu Waste Bank, Sambung Jawa Village, uses an empowerment model for local community development by emphasizing community participation.